Mid Jurassic (Late Callovian) dinoflagellate cysts from the Lotena Formation of the Neuquén Basin, Argentina and their palaeogeographical significance - Riding, James B.; Quattrocchio, Mirta Elena; Martinez, Marcelo Adrian (Review of Palaeobotany and Palynology)
The Lotena Formation from two localities, Picún Leufú and Portada Covunco, in the Neuquén Basin of west-central Argentina was studied palynologically. The material examined produced moderately diverse Late Callovian dinoflagellate cyst assemblages. This age assignment is consistent with ammonite evidence. The dinoflagellate cyst floras are reminiscent of the Middle Jurassic associations of northwest Europe and surrounding areas. Marine palynomorphs typical of Australasia and the Arctic are absent. The similarity with Europe is strongly suggestive of an open marine connection between western Tethys and the Neuquén Basin during the Late Callovian. This is interpreted as being via the Hispanic Corridor, with the palynofloras being passively dispersed to the southwest by the circum-Tropical Marine Current. Earlier studies indicate that this trans-Pangean equatorial seaway first began to allow biotic interchange during the Mid Jurassic and this study proves that this open marine connection was established by the Late Callovian. The similarities between the dinoflagellate cyst assemblages of Europe and the Neuquén Basin are consistent with the distribution of other marine fossils and the existence of geographically continuous marine facies belts. © 2010. Fil: Riding, James B. British Geological Survey; Fil: Quattrocchio, Mirta Elena. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional del Sur; Argentina Fil: Martinez, Marcelo Adrian. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional del Sur; Argentina